1989
DOI: 10.1111/j.1745-4549.1989.tb00109.x
|View full text |Cite
|
Sign up to set email alerts
|

EFFECTIVENESS of ORGANIC CHELATORS IN SOLUBILIZING CALCIUM AND ZINC IN FORTIFIED CEREALS UNDER SIMULATED GASTROINTESTINAL pH CONDITIONS

Abstract: The effectiveness of various chelating agents on the solubilization of zinc and calcium, in a calcium‐fortified wheat flake cereal, has been evaluated using an in vitro method. This method is based on solubility during a sequential pH treatment simulating gastrointestinal conditions (endogenous pH of cereal, to pH 2, to pH 7.5). Zinc oxide was added to the cereal at 100% of the U. S. RDA for zinc, alone or in combination with the following organic chelators: citrate, malate, a combination of citrate and malate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
(20 reference statements)
0
6
1
Order By: Relevance
“…The rats consuming a diet with PA and yogurt had normal growth but sub-optimal zinc concentrations in bone and plasma. In contrast to previous studies by others (2, 7, 10, 32), in our study yogurt did not facilitate zinc absorption. The reason for this result remains unclear.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The rats consuming a diet with PA and yogurt had normal growth but sub-optimal zinc concentrations in bone and plasma. In contrast to previous studies by others (2, 7, 10, 32), in our study yogurt did not facilitate zinc absorption. The reason for this result remains unclear.…”
Section: Discussioncontrasting
confidence: 99%
“…The bacteria-induced fermentation process in yogurt reduces lactose to absorbable glucose, galactose and lactic acid (3638). Organic acids, such as lactic acid, have been shown to enhance zinc absorption by forming soluble ligands with zinc (2, 7, 10, 32). Lactic acid bacteria in sourdough cultures have been shown to degrade PA (39), and lactic acid fermentation increased some mineral solubility in vitro (2122).…”
Section: Discussionmentioning
confidence: 99%
“…However, it has also been suggested that although there is a slight increase in insoluble fiber during fermentation, soluble fiber decreases so that there is no net change in fiber content (14). The organic acids, such as lactic, acetic, butyric, propionic, and formic acids, produced during fermentation, may further potentiate zinc absorption by forming soluble ligands with zinc (2). Fermentation also reduces the energy required for cooking and improves the safety of the final food product because the reduced pH inhibits the growth of diarrheal pathogens during fermentation (9).…”
Section: Increase Intakes Of Foods Known To Enhance Zinc Absorptionmentioning
confidence: 99%
“…Certain amino acid-and cysteine-containing peptides, released during the digestion of cellular animal proteins (ie, from fish, chicken, and goat) and organic acids (eg, citric, lactic, acetic, butyric, and formic acids) produced during fermentation, enhance zinc absorption, possibly by forming soluble ligands with zinc or by preventing the formation of the insoluble zinc-phytate complex (2,3).…”
Section: Increase Intakes Of Foods Known To Enhance Zinc Absorptionmentioning
confidence: 99%
See 1 more Smart Citation